SINERGISITAS INSTANSI PEMERINTAH DAERAH DALAM PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN ROKAN HILIR PROVINSI RIAU PADA TAHUN 2015 - Ahmad, Fajar; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on the results of this study, it can be concluded that the synergicity of local government agencies in the handling of forest and land fires in Rokan Hilir Regency in 2015 has not been effective. Forest and land fires are handled by the related agencies, namely BPBD, BAPEDAL and the Forest Service, which are still in short supply, where forest fires are still occurring and the fire extinguishing process is still slow. Synergicity is essentially an interaction of two or more parties that interact and interact dynamically to achieve common goals. The creation of good governance will never be separated from the synergy between stakeholders to achieve common goals.The importance of the synergicity of local government agencies in combating forest and land fires is to be able to plan in an integrated manner and to follow up on any existing issues. With the synergy of local government agencies are expected to quickly solve the problems of forest fires that often occur in Rokan Hilir District.This study aims to determine the synergicity of local government agencies in dealing with forest fires and land Rokan Hilir District. This study uses qualitative research methods with descriptive research type, which can be interpreted as a problem-solving process investigated by describing the state of research subjects based on the facts that appear during the study which then continued with based on existing theories.Keywords: Synergy, Government Agencies, Fire Prevention